Pengelolaan dan Analisis Nilai Tambah By-Products Industri Gula (Studi Kasus di Pabrik Gula Gempolkrep, Mojokerto, Jawa Timur) - Relita Novianti; Yusman Syaukat; Meti Ekayani (Institut Pertanian Bogor, 2021)
The sugar industry is one of the agriculture-based industries which use sugar cane as a raw material to produce sugar. The processing of sugar cane into sugar generates by-products such as bagasse, molasses, and filter cake which will cause environmental pollution if they are untreated. This research identified the utilization pattern of sugar industry by-products in Gempolkrep Sugar Factory and analyzed the added value from by-products utilization using Hayami Method. Based on the utilization pattern at Gempolkrep Sugar Factory, bagasse is used as an alternative raw material for electricity generation. Filter cake is used as raw material for compost fertilizer. Molasses is used as a raw material for bioethanol manufacture. The added value obtained from processing filter cake into compost is IDR141.335 per ton, while bioethanol products from molasses provide an added value of IDR752.645 per ton. Keywords: bagasse, bioethanol, filter cake, Hayami method, molasses, value added